Integrating electrospun aligned fiber scaffolds with bovine serum albumin-basic fibroblast growth factor nanoparticles to promote tendon regeneration - Yuwan Li; Zhen Ge; Ziming Liu; Longfei Li; Jian Song; Hongde Wang; Feng Tian; Pengfei Lei; Long Li; Jiajia Xue (Journal of Nanobiotechnology)
Abstract Background Electrospun nanofiber scaffolds have been widely used in tissue engineering because they can mimic extracellular matrix-like structures and offer advantages including high porosity, large specific surface area, and customizable structure. In this study, we prepared scaffolds composed of aligned and random electrospun polycaprolactone (PCL) nanofibers capable of delivering basic fibroblast growth factor (bFGF) in a sustained manner for repairing damaged tendons. Results Aligned and random PCL fiber scaffolds containing bFGF-loaded bovine serum albumin (BSA) nanoparticles (BSA-bFGF NPs, diameter 146 ± 32 nm) were fabricated, respectively. To validate the viability of bFGF-loaded aligned PCL nanofiber scaffold (aPCL + bFGF group) in tendon tissue engineering, we assessed the in vitro differentiation of human amniotic mesenchymal stem cells (hAMSCs) towards a tenogenic lineage and the in vivo regeneration of tendons using a rat Achilles tendon defect model. The encapsulated bFGF could be delivered in a sustained manner in vitro. The aPCL + bFGF scaffold promoted the in vitro differentiation of human amniotic mesenchymal stem cells (hAMSCs) towards a tenogenic lineage. In the repair of a rat Achilles tendon defect model, the aPCL + bFGF group showed a better repair effect. The scaffold offers a promising substrate for the regeneration of tendon tissue. Conclusions The aligned and random PCL fiber scaffolds containing bFGF nanoparticles were successfully prepared, and their physical and chemical properties were characterized. The aPCL + bFGF scaffold could promote the expression of the related genes and proteins of tendon-forming, facilitating tendon differentiation. In the rat Achilles tendon defect experiments, the aPCL + bFGF exhibited excellent tendon regeneration effects. Graphical Abstract